Pengaruh Bystander Effect, Moralias, Dan Asimetri Informasi Terhadap Kecenderungan Kecurangan Akuntansi - I Kadek Rocky Setiawan (Hita Akuntansi dan Keuangan, 2022)
This research was made in an effort to reveal the relationship between Bystander Effect, Individual Morality, and Information Asymmetry on Accounting Fraud Trends. BUMDes employees in Dawan Klungkung sub-district as many as 102 people were made into the population with 30 people selected as samples. This analysis uses multiple regression as an analytical technique with data collected through the stages of distributing questionnaires. The results of the study reveal that the Bystander Effect and information asymmetry can directly increase the possibility of fraud in BUMDes. Good individual morality can be used as a solution to reduce the possibility of fraud in institutions. Accounting fraud can go up or down influenced by 72.6% of the three variations of the independent variables in this study. In the future, this research can be used as material for consideration in making policies that are used to prevent fraud in a company.